Bacteriological study of diabetic foot ulcer according to Wagner’s classification: a one-year study - Malepati, Srikrishna; Vakamudi, Prakash; Kandati, Jithendra; Satish, Sreeram (International Surgery Journal, 2017)
Background: Diabetes is considered as one of the most important and rapidly evolving non-communicable disease which requires top priority around the world. 10-25% of diabetics develop foot infections [DFI’s] during the course of their disease period ranging from simple calluses to major Osteomyelitis. 3 Microbial infections of the diabetic foot ulcers are difficult to manage because of multiple factors associated in response including overall glycaemic control, associated complications like vascular disease and neuropathy. The present study was done to assess the microbial flora according to Wagner’s classification for diabetic foot disease. To isolate, identify the aerobic bacterial pathogens and their drug sensitivity pattern with reference to ESBL production Methods: A prospective study was conducted at a tertiary care hospital by department of general surgery among Diabetics presenting with diabetic foot infections. All the enrolled cases were classified based on Wagner’s classification and socio demographic data was noted. Specimens from the ulcer were collected and processed for isolation, identification of pathogens based on standard CLSI guidelines. The antibiotic sensitivity of the isolates was done and ESBL production was demonstrated by standard guidelines. Results: 346 cases were enrolled in study and grade-3 Wagner’s ulcers were predominant. Males were predominant, 46-55 years age group was common with mean age of 55.3±1.4 years. Peripheral arterial disease was more common than peripheral neuropathy and both were found significantly associated with development of ulcers. Methicillin resistant Staphylococcus aureus and Pseudomonas aeruginosa were most common isolates. MRSA exhibited maximum sensitivity to vancomycin, clindamycin and linezolid. Gram negative isolates exhibited maximum sensitivity to meropenems, piperacillin-tazobactam. The prevalence of ESBL producers in the study was 16.24%. Conclusions: DFI are a serious concern in uncontrolled diabetics and require proper management. Outcome of the infection depends upon the grading of the ulcer as per Wagner’s classification and also the nature of the infection either polymicrobial or with a single organism. Our study highlights and suggests that prospective multicentre studies are required to assess the appropriate antibiotic regimen in diabetic foot ulcers and proper management of antibiotics must be implemented to decrease the incidence and development of multi drug resistant organisms.